Probing hyperbolic and surface phonon-polaritons in 2D materials using Raman spectroscopy - Bergeron, Alaric; Gradziel, Clément; Leonelli, Richard; Francoeur, Sébastien (Nature communications, 2023)
The hyperbolic dispersion relation of phonon-polaritons (PhPols) in anisotropic van der Waals materials provides high-momentum states, directional propagation, subdiffractional confinement, large optical density of states, and enhanced light-matter interactions. In this work, we use Raman spectroscopy in the convenient backscattering configuration to probe PhPol in GaSe, a 2D material presenting two hyperbolic regions separated by a double reststrahlen band. By varying the incidence angle, dispersion relations are revealed for samples with thicknesses between 200 and 750 nm. Raman spectra simulations confirm the observation of one surface and two extraordinary guided polaritons and match the evolution of PhPol frequency as a function of vertical confinement. GaSe appears to provide relatively low propagation losses and supports confinement factors matching or exceeding those reported for other 2D materials. Resonant excitation close to the 1s exciton singularly exalts the scattering efficiency of PhPols, providing enhanced scattering signals and means to probe the coupling of PhPols to other solid-state excitations. Hyperbolic phonon polaritons (HPhPs) in anisotropic van der Waals materials hold promise for nanophotonic applications, but their far-field characterization remains challenging. Here, the authors demonstrate the application of Raman spectroscopy in a backscattering configuration to determine the dispersion of HPhPs in thin GaSe crystals.